Pengaruh Teknologi Informasi, Kemampuan Teknik Pengguna Terhadap Kinerja Sistem Informasi Akuntansi Pada PT. Varia Usaha Beton - Axanda Bilqis Prameswari; Wahyu Helmy Dimayanti Sukiswo (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The accounting information system is an evaluation of the application of the accounting information system used in a company to achieve the provision of accurate and effective accounting information in accordance with company objectives. The problem that occurs at PT Varia Usaha Beton is that the ups and downs of profit / loss are not optimal and fluctuate. This study aims to assess how information technology and user technical skills influence the performance of accounting information systems. This study uses descriptive statistical analysis and t-statistical tests, this study found that information technology has a significant and strong influence on the performance of accounting information systems with a path coefficient of 0.60 and p-value <0.1. In contrast, user technical ability shows an insignificant effect on the performance of accounting information systems with a path coefficient of 0.12 and a p-value of 0.23. Overall, information technology is proven to be a key factor in improving the performance of accounting information systems, while the influence of user technical skills requires further research. These results provide important implications for the management of PT Varia Usaha Beton to focus more on developing information technology to improve the performance of accounting information systems.